Management of treatment-related toxicities in advanced medullary thyroid cancer. (May 2018) - Brose, Marcia S.; Bible, Keith C.; Chow, Laura Q.M.; Gilbert, Jill; Grande, Carolyn; Worden, Francis; Haddad, Robert
Graphical abstract: Highlights: Vandetanib and cabozantinib play an important role in the treatment of advanced medullary thyroid cancer. These multikinase inhibitors are associated with toxicities that can be severe. Early recognition and management of adverse events are necessary to enable ongoing therapy at the highest tolerable dose for optimal clinical benefit. Abstract: Progress in the treatment of advanced medullary thyroid cancer (MTC) has resulted from the approval of 2 drugs within the past 5 years, vandetanib and cabozantinib. These multikinase inhibitors (MKIs) possess overlapping specificities for multiple kinase targets implicated in the progression of MTC. Both drugs are associated with toxicities, including hypertension, hemorrhage/perforation, diarrhea and other gastrointestinal events, several dermatologic events, and hypothyroidism. In addition, vandetanib is uniquely associated with QTc prolongation through interaction with myocardial potassium channels, and cabozantinib is uniquely associated with hand-foot skin reaction. Treatment-related toxicities occur frequently and can be severe or life-threatening, and patients undergoing long-term treatment will likely experience adverse events (AEs). Here we offer specific practical recommendations for managing AEs commonly occurring with vandetanib and cabozantinib. The recommended approach relies on early recognition and palliation of symptoms, dose interruption, and dose reduction as necessary in order for the patient to maintain the highest tolerable dose for as long as possible and optimal quality of life. Treatment guidelines do not specify a recommended sequence for treating with vandetanib and cabozantinib; however, most patients will receive both drugs during their lifetime. The choice for first-line therapy is individualized after a risk-benefit assessment and depends on physician preference and patient-related factors, such as comorbid conditions. Because most generalist practices may not be familiar with the intricacies of agents such as vandetanib and cabozantinib, we commend that patients with advanced MTC be managed and treated by a thyroid cancer specialist with coordination of care within a multidisciplinary team.